A Reflection on the Household, Income and Labour Dynamics in - Richardson, S (My University, 2013)
HILDA is a powerful lady. By the age of 10, she had already produced over 300 journal articles,about 30 books and book chapters and multiple public reports and working papers. She had stimulated a step change in the sophistication of empirical analysis in the social sciences in Australia and provided the material for many a PhD thesis. She had provided governments and many interest groups with a genuine opportunity to use evidence as a foundation for policy-thinking. Who is the remarkable HILDA (her full name is Household, Income and Labour Dynamics in Australia Survey) and how has she accomplished so much in such a short time? HILDA is a panel dataset. That is, after interviewing a random sample of the Australian population in 2001, it resurveys the same people each year. Some of the questions are repeated every year, so a profile over time can be established for each individual (such as labour force behaviour). Others are repeated at intervals of several years (such as health status and behaviour). A few questions are specific modules that, to date, have only been asked once. As its name suggests, its main focus is on the labour market, income and family structures of Australian households and on how these evolve over time.
Keywords: Surveys and Survey Methodology; Policy; Surveys and Survey Methodology; Government, law and policy; Surveys and Survey Methodology; Policy; Government, law and policy